PROGRAM MATRIKULASI BAHASA ARAB DI PPB UIN WALISONGO SEMARANG - Anisa Alfurochmatin; Atik Syakiroh (Al-Mazaya: Jurnal Pendidikan Bahasa Arab, 2024)
The purpose of this research is to find out the Arabic matriculation program, especially for Postgraduate Students in 2023. UIN Walisongo Semarang requires new Postgraduate students to take the IMKA entrance test. Students who do not pass are encouraged to take language matriculation with the aim of improving their ability to face the test. The method used in this research is Qualitative Method with Descriptive Technique, meanwhile, the data collection technique is done through Literature Study and interviews with PPB officers or administrators and students who take the IMKA matriculation program. Based on the research conducted, it is concluded that the curriculum, teaching methods, the use of technology in learning, learning evaluation, are able to improve the score of Postgraduate Students of UIN Walisongo Semarang and the highest percentage of students who did not pass IMKA was S2 68.30% S3 31.70%. The largest department that did not pass was Islamic Studies. The comparison of all Postgraduate students is more who do not pass than those who pass. With a percentage of 23.13% passing and 76.87% not passing. Future research is expected to not only discuss the matriculation program but the programs provided by PPB UIN Waslisongo